2015
DOI: 10.3238/arztebl.2015.0452
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Well-Differentiated Thyroid Carcinoma

Abstract: SUMMARYBackground: Recent decades have seen a rise in the incidence of welldifferentiated (mainly papillary) thyroid carcinoma around the world. In Germany, the age-adjusted incidence of well-differentiated thyroid carcinoma in 2010 was 3.5 per 100 000 men and 8.7 per 100 000 women per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…The clinically relevant features that define the classical type of WDTC with a low risk of aggressiveness are pT1a solitary or multiple, N0/Nx, pT1b N0/Nx, pT2 N0/Nx, pT3>4 cm N0/Nx, tumor diameter below 4 cm and intrathyroid, R0 or R1 resection, and M0. The features connected with a high risk of WDTC are pT4 and M1 or R2 resection 12. However, on the basis of our own observation and subsequent postsurgical follow-up, this risk stratification does not always correspond with clinical outcome.…”
Section: Introductionmentioning
confidence: 71%
“…The clinically relevant features that define the classical type of WDTC with a low risk of aggressiveness are pT1a solitary or multiple, N0/Nx, pT1b N0/Nx, pT2 N0/Nx, pT3>4 cm N0/Nx, tumor diameter below 4 cm and intrathyroid, R0 or R1 resection, and M0. The features connected with a high risk of WDTC are pT4 and M1 or R2 resection 12. However, on the basis of our own observation and subsequent postsurgical follow-up, this risk stratification does not always correspond with clinical outcome.…”
Section: Introductionmentioning
confidence: 71%
“…Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer and accounts for approximately 80- 85% of malignant neoplasms of the thyroid gland. It has a 10-year survival rate 93% in the United States, which is relatively favorable compared to that of malignant tumors [ 1 ]. The major factors underlying the prognosis of PTC include patient age, gender, tumor size, histological findings, extrathyroidal extension, clinical lymph node metastasis and remote metastasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two drugs were recently applied in the treatment of these tumors, where they have shown that they prolong progression free-survival, but not the overall survival. 35 In general, all the anti-VEGF drugs that were applied in recent clinical trials, have limited therapeutic success in TC, due to low response rate 36 and adverse effects in various tissues and organs 37 . That is why it is necessary to conduct more investigations, which should be focused on molecular studies that could result in a novel antiangiogenesis therapy as an effective treatment for thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%